Association of Protein and Vitamin D Intake With Biochemical Markers in Premature Osteopenic Infants: A Case-Control Study - Mohamed, Mohamed; Kamleh, May; Muzzy, Julia; Groh-Wargo, Sharon; Abu-Shaweesh, Jalal (Frontiers in Pediatrics, 2020)
Osteopenia (OP) in preterm infants remains an important challenge and largely dependent on nutritional postnatal intake of factors influencing bone mineralization. We conducted a prospective case-control study to evaluate the importance of protein and vitamin D intake in OP among neonates with birth weight <1250 g. Simultaneous serum parathyroid hormone (PTH), alkaline phosphatase (ALP), calcium (Ca), phosphorus (P), vitamin D and protein levels were measured during the first 6 weeks postnatally. At 6 weeks of age, OP was evaluated using wrist radiographs. Comparisons were analyzed using multivariate linear regression, receiver operating characteristic curves, χ2 and Wilcoxon Rank Sum. Of the 26 premature infants enrolled, 13 developed radiographic OP. Daily protein intake (coef=-0.40, p=0.001) and vitamin D concentrations (21 ± 5.7ng/ml) were significantly lower in the OP group compared to non-OP subjects. ALP concentration exceeding 619 IU/L, sensitivity of 76.9% and specificity of 75%, was predictive of osteopenia at 6 weeks postnatally. PTH levels were higher at 6 weeks in osteopenia subjects (193 ± 102.5 pg/ml, p<0.001) compared to non-osteopenia subjects. The findings in this study support the role of vitamin D and protein intake in osteopenia risk of VLBW infants and inform future practice and research on best practices for OP management.